Limits to the European Union's Normative Power in a Post-conflict Society: EULEX and Peacebuilding in Kosovo - Zupančič, Rok (SpringerBriefs in Population Studies, 2018)
Peacebuilding; EULEX; Kosovo; European Union; Conflict prevention; Normative power; Post-conflict; IECEU